THE SCHOOL DIRECTOR SROLES ON DEVELOPING CURRICULUM AND LEARNNING MANAGEMENT - Loeknok, Phakcapohn; Kositpimanvach, Ekkarach (Journal of Graduate MCU KhonKaen Campus, 2021)
This academic article involves the information about the roles of school directors on developing curriculum and learning management in order to adjust the contents that are proper and responsive to changes in politics, economy, society and technology which is considered as the important part of education system. The school directors are responsible for setting guidelines on learning management in order to succeed the school objectives. The most effective curriculum needs to be developed continuously. The school director’s roles in curriculum development are as follow: 1) Analyzing basic information, 2) Setting the objectives of the curriculum, 3) Specifying the contents and learning experiences and 4) applying the curriculum. The roles of school directors on teachers’ learning management are 1) to encourage and support teachers’ learning management, 2) to develop instructional media and learning facilities and 3) to encourage and develop students’ learning experiences.